A Comparison Between Global Nutrient Retention Models for Freshwater Systems - Zhou, Jinhui; Scherer, Laura; van Bodegom, Peter M.; Beusen, Arthur H. W.; Mogollón, José M. (Frontiers in Water, 2022)
Against the backdrop of increasing agricultural production, population, and freshwater/coastal eutrophication, studies are aiming to understand the behavior of nitrogen (N) and phosphorus (P) in the global freshwater system. Global nutrient models are typically used to quantify the nutrient amount and content in freshwater systems across different river orders and catchments. Such models typically use empirically derived nutrient retention equations for predicting nutrient fate, and these equations may be derived using data from a specific region or environment or for a specific context. Here we used IMAGE-GNM, a spatially explicit nutrient model at a half-degree resolution, to examine the performance of several well-known empirical equations by comparing the respective model outcomes with observed data on a global scale. The results show that 1) globally, the empirical retention equations work better for predicting N fate than P fate; 2) hydraulic drivers are the most important factor affecting the residual of total N and P concentrations, compared with the functional forms and the coefficients in the empirical equations. This study can aid in assessing the variability and accuracy of various retention equations from regional to global scales, and thus further strengthen our understanding of global eutrophication.